Textures and patterns of space. Images of the temporary and of the human and spatial infinity (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2020)
In the terrestrial landscape each path defines the image of a possible direction and along its course the points that intersect it and interrupt it define the distance. Thus, the trace marked on the earth draws and orders the terrestrial landscape first, creating a dimensional and formal relationship between the void and the horizon, and then the urban landscape, when it penetrates into the void created by creating thick warps that are configured as geometric maps and mental. The layouts define the density and the rarefaction of the space generating images of emptiness and fullness. The terrestrial and urban layout brings with it the narration of space and the relationship between space and man. It brings with it the real finite and the perceived infinity, the image of the world and of the earth, how one lives, how one lives. In the immense, desert and extensive spaces, the path is broken by different signs, unrelated to living. Signs that however accompany man’s life, his being able to inhabit the world. Thus, along the endless land traces of simple filling stations, they become functional intersections and functional limits, reminding us of the need to organize life even in a vacuum. These tracks create clear and indelible images, able to tell about man and space, life and space of life, but also society and development together with the will to survive on earth. Through a graphic, photographic and literary survey, this work intends to study and reveal the plots that generate space and the paths in which space, empty and full, is formed and transformed, creating infinite images that extend the spatial temporality to infinity.
Keywords: Earth landscape; spatial and human paths; time and space